2012
DOI: 10.2131/jts.37.539
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the testicular toxicity of prenatal exposure to bisphenol A based on microarray analysis combined with MeSH annotation

Abstract: Bisphenol A (BPA) is known to be an endocrine disruptor that affects the development of reproductive system. The aim of the present study was to investigate a group of testicular genes dysregulated by prenatal exposure to BPA. Pregnant ICR mice were treated with BPA by subcutaneous administration on days 7 and 14 of pregnancy. Tissue and blood samples were collected from 6-week-old male offspring. Testes were subjected to gene expression analysis using a testis-specific microarray (Testis2), consisting of 2,48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 43 publications
1
29
0
2
Order By: Relevance
“…The testosterone concentration increased in 9-week-old male pups exposed to BPA in utero and through lactation (Watanabe et al 2003 ), and this could be attributed to in utero BPA-induced proliferative activity (mitogenic effect) on testosterone-producing Leydig cells (Nanjappa et al 2012 ). In addition to modulating the Leydig cells, BPA also induced downregulation of several genes associated with Sertoli cell function (Msi1h, Ncoa1, Nid1, Hspb2, and Gata6) in 6-week-old male mice after prenatal exposure (Tainaka et al 2012 ), thereby disrupting the blood-testis barrier (BTB) and impairing spermatogenesis Su et al 2011 ). Perturbation of BTB (reduction in the expression of Connexin 43 and increases in the expression of N-cadherin and Zona Occludin-1) and spermatogenesis were also observed in 45/90-day-old rats neonatally exposed to BPA (≥400 μg/kg bwt/day, during PND 1-5) (Salian et al 2009b ).…”
Section: Effects Of In Utero Exposure To Bisphenol a On Male Reproducmentioning
confidence: 95%
“…The testosterone concentration increased in 9-week-old male pups exposed to BPA in utero and through lactation (Watanabe et al 2003 ), and this could be attributed to in utero BPA-induced proliferative activity (mitogenic effect) on testosterone-producing Leydig cells (Nanjappa et al 2012 ). In addition to modulating the Leydig cells, BPA also induced downregulation of several genes associated with Sertoli cell function (Msi1h, Ncoa1, Nid1, Hspb2, and Gata6) in 6-week-old male mice after prenatal exposure (Tainaka et al 2012 ), thereby disrupting the blood-testis barrier (BTB) and impairing spermatogenesis Su et al 2011 ). Perturbation of BTB (reduction in the expression of Connexin 43 and increases in the expression of N-cadherin and Zona Occludin-1) and spermatogenesis were also observed in 45/90-day-old rats neonatally exposed to BPA (≥400 μg/kg bwt/day, during PND 1-5) (Salian et al 2009b ).…”
Section: Effects Of In Utero Exposure To Bisphenol a On Male Reproducmentioning
confidence: 95%
“…In vitro studies have shown that BPA can interact with estrogen receptors α and β, leading to estrogenic effects [3], and act as an androgen receptor antagonist with strong anti-androgenic effects [4]. The endocrine-disrupting effects of BPA on male reproductive health have raised concerns over the past decades and a number of animal studies have shown that low environmental levels of BPA exposure can cause adverse effects on male reproduction [5,6]. In humans, several studies have demonstrated associations between BPA and semen quality parameters or reproductive hormones [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These behavioral disruptions are strongly correlated with a range of molecular, physiological, and organ-level mechanisms involved in sex-dependent behaviors, e.g., brain ER gene expression (rat: Cao et al 2013), fetal ovarian and gonadal development (fish: Chung et al 2011; mice: Kundakovic et al 2013; Tainaka et al 2012; Xi et al 2011a, 2011b; rat: Cao et al 2013; sheep: Veifa-Lopez et al 2013), pituitary and gonadotrophin development (mice: Brannick et al 2012), brain and gonadal enzyme activity (rat: Nanjappa et al 2012), altered hypothalamic-pituitary-gonadal (HPG) axis activity (mice: Xi et al 2011a; rats: Ramos et al 2003), and circulating testosterone levels (mice: Tanaka et al 2006). In contrast, several studies were not able to identify correlations between BPA-induced mechanistic effects and behavioral disruptions (mice: Palanza et al 2002; Cagan et al 1999; rat: Kobayashi et al 2012; Ryan et al 2010) or differences between sexes in BPA-induced learning deficits (fish: Saili et al 2012).…”
Section: Introductionmentioning
confidence: 99%